"Reskilling" through self-representation: Digital story-telling as an alternative English Experience for Chinese International Students in Australia - Zhang, He; Gong, Qian (Peter Lang, 2020)
In January 2019, a Duke University administrator’s email titled “To Speak English or To Not Speak English …” warned Chinese international students in a biostatistics master’s program not to use their mother tongue in common areas. The email stirred wide concern across social media in the United States (US) and China (“Outcry after Duke’s Warning”, 2019). In it, the graduate studies director said that speaking Chinese during breaks was a sign of not practicing English, which Chinese students are supposed to do while studying in the US. The director stated that doing so might damage their work opportunities in the faculty and said they should keep these unintended consequences in mind when they choose to speak in Chinese in the building. Rather than seeing Chinese students’ bilingual and intercultural abilities as an intellectual advantage, the director believed English to be the only language useful for study in the US, and any lack of it as equal to academic incompetence. The incident sounds the alarm that a discourse of power is influential for our perception of language, which may result in deeper language inequalities and educational inequalities between the West and the rest of the world. Even Duke University, which is renowned worldwide and is diverse in ethnic representation (65% of students in the program mentioned were from China, as The Guardian’s report said), cannot be an exception.